The Impact of HVAC Systems on Speech Intelligibility in University Classrooms - OKTAV, Akın; ENER, Arda; ÖZENÇ, Faruk; SARI, Sıla (Archives of Acoustics, 2025)
Good speech intelligibility in university classrooms is crucial to the learning process, ensuring that students can clearly hear all conversations taking place in the classroom. While it is well known that speech intelligibility depends on the geometrical characteristics of a space and the properties of its surfaces, other factors need also to be considered. Among the most important are: the heating, ventilation, and air conditioning (HVAC) systems used in classrooms. Fan noise from HVAC systems increases the background noise level (BNL), negatively affecting speech intelligibility. In addition, the movement of air caused by these systems alters room acoustic variables. Although this dynamic situation is often overlooked in the early design stages, HVAC systems are often active during lectures and influence acoustics variables, especially the speech transmission index (STI). In this study, the impact of HVAC systems on the STI was measured in five different unoccupied classrooms in the Rafet Kayıș Faculty of Engineering at Alanya Alaaddin Keykubat University. The results were evaluated according to relevant standards. The results of these evaluations offer insights for researchers, architects, and engineers working in the field of acoustics.